Reminiscences of Professor Shanti Lal Kayastha - Mohan, Anand; Mohan, Arvind (National Geographical Journal of India, 2022)
The spirit force behind this beautifully composed “Kulgeet” of Banaras Hindu University was adopted by our father in letter & spirit and he led a pious and peaceful life in the holy city of Varanasi. Our father maintained a highly disciplined routine throughout his life span. ‘Early to bed, early to rise’; a simple living and high thinking and frugal life style were his standard yardstick. Offering morning prayers, listening to BBC radio news, long morning walk, reading editorial column of the "The Statesman Newspaper" and scribbling diary in beautiful handwriting made a fine start of his day. He encouraged us to learn Hindi and advocated for a Hindi daily newspaper. Apart from academics, he had a passion for photography, was an enthusiastic swimmer who crossed Ganga in one go and started Boat & Swimming club of BHU as its chairman. The typewriter remained as his handy companion along with rich collection of National Geographic magazines, Reader's Digest and Mont Blanc pens. The biggest attractions for all of us were his lively discussions during dinner at the dining table. Father would talk on wide ranging topics which everybody always eagerly looked for. He inculcated in us fine habits of dining together. While eating, he desired that family should talk on different issues rather than involve in newspaper or magazine reading, watching T.V. etc. Much of the narration in the following pages is a consequence of the information we have gathered over a period of time during such family dinner culture.